Informal supply chains of wild meat from rural Amazonia and food security in an urban center - Fiorella Briceño Huerta; Michael P. Gilmore; Mark Bowler; Brian M. Griffiths (Conservation Biology, 2026)
Iquitos, the most populated city in the Peruvian Amazon, is a hub in the regional supply chain of wild meat and supplies urban consumers. Studies on wild meat consumption have focused primarily on markets, limiting the scope of species considered to those that are economically valuable and potential inferences from those data. We conducted interviews with 1548 households in Iquitos across all four districts to assess wild meat consumption rates for 7831 people in those households. We used species‐ and source‐specific conversion factors to estimate biomass consumed from different species and sources in the supply chain. We estimated that 1786 t (95% CI 636.48–3317.62) of wild mammal meat were consumed in 2019 in Iquitos, which is about 4.25 kg (95% CI 1.54–8.02) per person per year. Markets supplied 57.22% of all wild mammal meat, but 14.67% was purchased from other sources and 27.85% was not purchased. Paca ( Cuniculus paca ) and collared peccary ( Dicotyles tajacu ) were the most heavily consumed species, mostly from markets. The majority of meat from other species, such as the woolly monkey ( Lagothrix lagotricha ) and capybara ( Hydrochoerus hydrochaeris ), was traded outside markets. Our results indicated that wild mammal consumption rates may be much higher in Iquitos than previously reported, likely because social connections accounted for about half of the supply chain; consumers are receiving wild meat as gifts or were hunting themselves. The breadth of mammal meat consumption demonstrates the contributions of hunting to the food security and economic stability of consumers in Iquitos and the potential for sustainable supply chains of some mammals.

Differences in PFAS exposure between Pacific pinnipeds: The Galapagos (Zalophus wollebaeki) and California (Zalophus californianus) sea lions - Ashley E. Cave; Isabella G. Livingston; Taylor M. Gregory; Eleanor C. Hawkins; Shelly Vaden; Marjorie Riofrío-Lazo; Diane Deresienski; Gregory A. Lewbart; Anthony J. Orr; Emily Griffith; Christopher Fuller; Mark J. Strynar; et al. (Marine Pollution Bulletin, 2026)

Pathways and processes controlling the distribution of anthropogenic lead in the interior of the Southern Ocean - Alex Griffiths; Yee-Lap Leung; Andrew R. Bowie; Melanie East; Mark Rehkämper; Tina van de Flierdt (Geochimica et Cosmochimica Acta, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Source-sink dynamics facilitate mammal recovery after unsustainable hunting in a community-managed natural protected area in the Peruvian Amazon - Brian M. Griffiths; Ellen Nirenblatt; Chelsie Romulo; Mark Bowler; Fiorella Briceño Huerta; Michael P. Gilmore (Ambio, 2026)

Spatial extent and age-related bioaccumulation of fluoride in the bones of house sparrows around aluminium smelting operations - Max M. Gillings; Riccardo Ton; Phoebe Lewis; Minna Saaristo; Mark Patrick Taylor; Simon C. Griffith (Environmental Research, 2025)

Telomere length declines with mean blood lead concentration in an urban passerine - Heung Ying Janet Chik; Max M. Gillings; Riccardo Ton; Marco van der Velde; Mark Patrick Taylor; John P. Swaddle; Hannah L. Dugdale; Simon C. Griffith (Environmental Research, 2025)

Socioeconomic drivers of wild meat consumption in the city of Iquitos, Peru - Fiorella Briceño Huerta; Michael P. Gilmore; Mark Bowler; Brian M. Griffiths (Conservation Biology, 2025)
Wild meat represents a vital source of micro‐ and macronutrients for forest‐dwelling people; however, city dwellers with access to animal protein from different animals may also consume large amounts of wild meat as part of their customs and traditions, to diversify their diets, to maintain connections to their rural kin, and to access meat without having to pay the high prices of domestic meat in the city. The aggregate urban and rural demand for wild meat consumption demonstrates a great risk for overhunting highly preferred and vulnerable species and degrading already fragile Amazonian ecosystems and the food security of people in rural areas. We assessed the effects of socioeconomics factors on wild meat consumption in the city of Iquitos in the Peruvian Amazon. We conducted 1548 interviews with consumers across the city of Iquitos and collected socioeconomic and wild meat consumption data. We used a double hurdle model to estimate simultaneously the probability of a consumer eating wild meat each week and their consumption rate based on 10 variables. In final parsimonious models, monthly income, location in the city (district and distance to market), amount of education, and amount of time spent in Iquitos were all important factors determining consumption rate. We predicted that consumption rates would vary across the city and in some areas would be as high as >7 kg·person −1 ·year −1 . The spatial distribution of wild meat consumption showed that people in newer, rapidly growing parts of the city consumed more wild meat and were therefore more dependent on sustainable supply chains. We recommend that consumers who have very high predicted consumption rates may be useful targets for conservation efforts to reduce that consumption, such as culturally relevant, informal educational programs. In our study, these people migrated from rural areas and live along the Iquitos–Nauta Road and are wealthy consumers in downtown Iquitos.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Ultrasound image abnormalities associated with the development of ovine pulmonary adenocarcinoma - David Collie; James Meehan; Helen Brown; Ziyuan Chang; Chris Cousens; Jo Moore; Helen Todd; David J. Griffiths; Nicole Storer; Chad E. Eckert; Mark Gray (Research in Veterinary Science, 2025)

Exposure to lead (Pb) contamination heightens predator avoidance behaviours in an urban bird - Heung Ying Janet Chik; Joseph F. Di Liberto; Max M. Gillings; Riccardo Ton; Mark Patrick Taylor; John P. Swaddle; Simon C. Griffith (Animal Behaviour, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Attentional bias to alcohol-related cues: effects of menstrual cycle phase and sex differences - Annie K. Griffith; Michelle M. Martel; Mark T. Fillmore (Psychopharmacology, 2025)

An island of receptor-like genes at the Rrs13 locus on barley chromosome 6HS co-locate with three novel sources of scald resistance - Peter E. Eckstein; Lindsay J. Griffith; Xiang M. Zhang; T. Kelly Turkington; Mark G. Colin; Samuel Holden; Sean Walkowiak; Gurcharn S. Brar; Aaron D. Beattie (Theoretical and Applied Genetics, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Blood lead increases and haemoglobin decreases in urban birds along a soil contamination gradient in a mining city - Max M. Gillings; Riccardo Ton; Tiarne Harris; Mark Patrick Taylor; Simon C. Griffith (Environmental Research, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Engagement in sustainable horticulture is associated with greater perceived health benefits amongst gardeners - Chloe Sutcliffe; Lauriane Suyin Chalmin-Pui; Mark Baudert Gush; Alistair Griffiths (Urban Forestry & Urban Greening, 2024)

Neodymium isotope composition and rare earth element distribution of East Antarctic continental shelf and deep waters - Alex Griffiths; Myriam Lambelet; Kirsty Crocket; Richard Abell; Barry J. Coles; Katharina Kreissig; David Porter; Frank O. Nitsche; Mark Rehkämper; Tina van de Flierdt (Chemical Geology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Differentiation of self, emotion management skills, and nomophobia among smartphone users: The mediating and moderating roles of intolerance of uncertainty - Mustafa Ercengiz; Banu Yildiz; Mustafa Savci; Mark D. Griffiths (The Social Science Journal, 2024)

Sofalizing and its relationship with social media addiction and psychosocial factors: A new phenomenon among emerging adults - Şule Betül Tosuntaş; Engin Karadağ; Emrah Emirtekin; Kagan Kircaburun; Mark D. Griffiths (The Social Science Journal, 2024)

Remedial effectiveness of a pond biomanipulation: Habitat value and concentrations of polychlorinated biphenyls in fish - Rebecca A. Efroymson; Mark J. Peterson; R. Trent Jett; Natalie A. Griffiths; Evin T. Carter; Allison M. Fortner; Christopher R. DeRolph; Peijia Ku; Paul G. Matson; Rachel M. Pilla; Teresa J. Mathews (Journal of Hazardous Materials, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

For R-eel?! Investigating international sales of critically endangered species in freshwater eel products with DNA barcoding - Amy Goymer; Kristen Steele; Freddie Jenkins; Gemma Burgess; Lucy Andrews; Nina Baumgartner; Chrysoula Gubili; Andrew Mark Griffiths (Food Control, 2023)

Experimental investigation of a multilayer detention roof for stormwater management - Mohammad A. Alim; Sayka Jahan; Ataur Rahman; Mohammad Ataur Rahman; Mark Liebman; Brad Garner; Robert Griffith; Merran Griffith; Zhong Tao (Journal of Cleaner Production, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The role of healthy emotionality in the relationship between fear of COVID-19 and mental health problems: a cross-sectional study - Ni Yao; Nabi Nazari; Hassan Ali Veiskarami; Mark D. Griffiths (Cognitive Processing, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Prevalence of Poor Sleep Quality and Its Determinants Among Bangladeshi Students: A Pilot Study - Mohammed A. Mamun; Md. Sharif Hossain; Md. Kamruzzaman; Md. Ibrahim Khalil; Md. Tajuddin Sikder; Md. Dilshad Manzar; Mark D. Griffiths (Sleep and Vigilance, 2020)

Factors Affecting Sleep Quality Among the University Students in Bangladesh: A Cross-Sectional Structured Interview Study - Md. Sabbir Ahmed; Safayet Khan; Kamrul Hsan; Liton Chandra Sen; Fakir Md Yunus; Mark D. Griffiths (Sleep and Vigilance, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge - Sarah M. Griffiths; Evelyn D. Taylor-Cox; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Biodiversity and Conservation, 2020)
Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservation genetics approach to inform restoration and management of the loggerhead sponge ( Spheciospongia vesparium ) in the Florida Keys, USA. This species is a dominant, habitat-forming component of marine ecosystems in the Caribbean region, but in Florida has suffered numerous mass mortality events. We developed microsatellite markers and used them to genotype sponges from 14 locations in Florida and a site each in The Bahamas, Belize and Barbuda. We found that genetic diversity levels were similar across all sites, but inbreeding and bottleneck signatures were present in Florida. Populations are highly structured at the regional scale, whilst within Florida connectivity is present in a weak isolation by distance pattern, coupled with chaotic genetic patchiness. Evidence of a weak barrier to gene flow was found in Florida among sites situated on opposite sides of the islands in the Middle Keys. Loggerhead sponge populations in Florida are vulnerable in the face of mass mortalities due to low connectivity with other areas in the region, as well as distance-limited and unpredictable local connectivity patterns. However, our discovery of Florida’s high genetic diversity increases hope for resilience to future perturbations. These results provide valuable insight for sponge restoration practice in Florida.

Internet addiction and sleep quality: a response to Jahan et al. (2019) - Mohammed A. Mamun; Mark D. Griffiths (Sleep and Biological Rhythms, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Shear stress and blood trauma under constant and pulse-modulated speed CF-VAD operations: CFD analysis of the HVAD - Zengsheng Chen; Sofen K. Jena; Guruprasad A. Giridharan; Michael A. Sobieski; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Medical & Biological Engineering & Computing, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Isotopic evidence of biotrophy and unusual nitrogen nutrition in soil‐dwelling Hygrophoraceae - Hans Halbwachs; Gary L. Easton; Roland Bol; Erik A. Hobbie; Mark H Garnett; Derek Peršoh; Liz Dixon; Nick Ostle; Peter Karasch; Gareth W. Griffith (Environmental Microbiology, 2018)
Summary Several lines of evidence suggest that the agaricoid, non‐ectomycorrhizal members of the family Hygrophoraceae (waxcaps) are biotrophic with unusual nitrogen nutrition. However, methods for the axenic culture and lab‐based study of these organisms remain to be developed, so our current knowledge is limited to field‐based investigations. Addition of nitrogen, lime or organophosphate pesticide at an experimental field site (Sourhope) suppressed fruiting of waxcap basidiocarps. Furthermore, stable isotope natural abundance in basidiocarps were unusually high in 15 N and low in 13 C, the latter consistent with mycorrhizal nutritional status. Similar patterns were found in waxcap basidiocarps from diverse habitats across four continents. Additional data from 14 C analysis of basidiocarps and 13 C pulse label experiments suggest that these fungi are not saprotrophs but rather biotrophic endophytes and possibly mycorrhizal. The consistently high but variable δ 15 N values (10–20‰) of basidiocarps further indicate that N acquisition or processing differ from other fungi; we suggest that N may be derived from acquisition of N via soil fauna high in the food chain.

Potentially infanticidal behavior in the Amazon river dolphin (Inia geoffrensis) - Mark T. Bowler; Brian M. Griffiths; Michael P. Gilmore; Andrew Wingfield; Maribel Recharte (acta ethologica, 2018)

Endocytic Uptake, Transport and Macromolecular Interactions of Anionic PAMAM Dendrimers within Lung Tissue - Christopher J. Morris; Ghaith Aljayyoussi; Omar Mansour; Peter Griffiths; Mark Gumbleton (Pharmaceutical Research, 2017)

Erratum to: Mechanistic insight of platelet apoptosis leading to non-surgical bleeding among heart failure patients supported by continuous-flow left ventricular assist devices - Nandan K. Mondal; Tieluo Li; Zengsheng Chen; Hegang H. Chen; Erik N. Sorensen; Si M. Pham; Michael A. Sobieski; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Molecular and Cellular Biochemistry, 2017)

Mechanistic insight of platelet apoptosis leading to non-surgical bleeding among heart failure patients supported by continuous-flow left ventricular assist devices - Nandan K. Mondal; Tieluo Li; Zengsheng Chen; Hegang H. Chen; Erik N. Sorensen; Si M. Pham; Michael A. Sobieski; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Molecular and Cellular Biochemistry, 2017)

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Modeling What We Sample and Sampling What We Model: Challenges for Zooplankton Model Assessment - Jason D. Everett; Mark E. Baird; Pearse Buchanan; Cathy Bulman; Claire Davies; Ryan Downie; Chris Griffiths; Ryan Heneghan; Rudy J. Kloser; Leonardo Laiolo; Ana Lara-Lopez; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2017)

Diurnal Fluctuations in Acidification and Hypoxia Reduce Growth and Survival of Larval and Juvenile Bay Scallops (Argopecten irradians) and Hard Clams (Mercenaria mercenaria) - Christopher J. Gobler; Hannah R. Clark; Andrew W. Griffith; Mark W. Lusty (Frontiers in Marine Science, 2017)

Sex steroid profiles and pair-maintenance behavior of captive wild-caught zebra finches (Taeniopygia guttata) - Nora H. Prior; Kang Nian Yap; Hans H. Adomat; Mark C. Mainwaring; H. Bobby Fokidis; Emma S. Guns; Katherine L. Buchanan; Simon C. Griffith; Kiran K. Soma (Journal of Comparative Physiology A, 2016)

Activation and shedding of platelet glycoprotein IIb/IIIa under non-physiological shear stress - Zengsheng Chen; Nandan K. Mondal; Jun Ding; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Molecular and Cellular Biochemistry, 2015)

Assessing Landscape Change and Processes of Recurrence, Replacement, and Recovery in the Southeastern Coastal Plains, USA - Mark A. Drummond; Michael P. Stier; Roger F. Auch; Janis L. Taylor; Glenn E. Griffith; Jodi L. Riegle; David J. Hester; Christopher E. Soulard; Jamie L. McBeth (Environmental Management, 2015)

Principles and application of LIMS in mouse clinics - Holger Maier; Christine Schütt; Ralph Steinkamp; Anja Hurt; Elida Schneltzer; Philipp Gormanns; Christoph Lengger; Mark Griffiths; David Melvin; Neha Agrawal; Rafael Alcantara; Arthur Evans; et al. (Mammalian Genome, 2015)

Genetic evidence from the spiny lobster fishery supports international cooperation among Central American marine protected areas - Nathan K. Truelove; Sarah Griffiths; Kim Ley-Cooper; James Azueta; Isaias Majil; Stephen J. Box; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Conservation Genetics, 2015)

On the state of the knowledge of rainfall extremes in the western and northern Pacific basin - Michael C. Kruk; Andrew M. Lorrey; Georgina M. Griffiths; Mark Lander; Ethan J. Gibney; Howard J. Diamond; John J. Marra (International Journal of Climatology, 2015)
The relevant literature on extreme rainfall events in the Pacific remains relatively sparse compared to other regions (e.g. the coterminous United States, Europe, etc.). Moreover, several recent reports on climate in the Pacific mention the paucity of extremes information and often list ‘trends in historical climate’ as a necessary next step. This scientific assessment meets this need by examining historical trends in and drivers of extreme rainfall events across the entire Pacific Basin, inclusive from Alaska southward to Australia, and longitudinally from the Philippines eastward to North America, with an emphasis on island and coastal locations (within 200 km of the coastline). There is evidence of a general decrease in the frequency of annual extreme rainfall events, yet the amount of extreme precipitation contributing to annual and seasonal totals appears to be on the rise. Region‐wide, the number of consecutive dry days is increasing for those locations that are already dry, while the number of consecutive wet days is increasing for the already wet locales. The data for extreme rainfall statistics are considered to be relatively high quality for trend detection, while the level of understanding of the physical causes behind extreme rainfall is positively high. Since the ability to analyze the changes in historical rainfall extremes with some confidence is relatively recent, understanding is expected to improve in the future with the advancement of new datasets and ‘climate reanalysis’ projects.

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Efficacy of novel sampling approaches for surveying specialised recreational fisheries - Shane P. Griffiths; Mitchell T. Zischke; Mark L. Tonks; Julian G. Pepperell; Sharon Tickell (Reviews in Fish Biology and Fisheries, 2013)

Erratum to: Molecular characterization of the translocation breakpoints in the Down syndrome mouse model Ts65Dn - Laura G. Reinholdt; Yueming Ding; Griffith J. Gilbert; Anne Czechanski; Jeffrey P. Solzak; Randall J. Roper; Mark T. Johnson; Leah Rae Donahue; Cathleen Lutz; Muriel T. Davisson (Mammalian Genome, 2011)

Molecular characterization of the translocation breakpoints in the Down syndrome mouse model Ts65Dn - Laura G. Reinholdt; Yueming Ding; Griffith T. Gilbert; Anne Czechanski; Jeffrey P. Solzak; Randall J. Roper; Mark T. Johnson; Leah Rae Donahue; Cathleen Lutz; Muriel T. Davisson (Mammalian Genome, 2011)

The bacterial biogeography of British soils - Robert I. Griffiths; Bruce C. Thomson; Phillip James; Thomas Bell; Mark Bailey; Andrew S. Whiteley (Environmental Microbiology, 2011)
Summary Despite recognition of the importance of soil bacteria to terrestrial ecosystem functioning there is little consensus on the factors regulating belowground biodiversity. Here we present a multi‐scale spatial assessment of soil bacterial community profiles across Great Britain (> 1000 soil cores), and show the first landscape scale map of bacterial distributions across a nation. Bacterial diversity and community dissimilarities, assessed using terminal restriction fragment length polymorphism, were most strongly related to soil pH providing a large‐scale confirmation of the role of pH in structuring bacterial taxa. However, while α diversity was positively related to pH, the converse was true for β diversity (between sample variance in α diversity). β diversity was found to be greatest in acidic soils, corresponding with greater environmental heterogeneity. Analyses of clone libraries revealed the pH effects were predominantly manifest at the level of broad bacterial taxonomic groups, with acidic soils being dominated by few taxa (notably the group 1 Acidobacteria and Alphaproteobacteria). We also noted significant correlations between bacterial communities and most other measured environmental variables (soil chemistry, aboveground features and climatic variables), together with significant spatial correlations at close distances. In particular, bacterial and plant communities were closely related signifying no strong evidence that soil bacteria are driven by different ecological processes to those governing higher organisms. We conclude that broad scale surveys are useful in identifying distinct soil biomes comprising reproducible communities of dominant taxa. Together these results provide a baseline ecological framework with which to pursue future research on both soil microbial function, and more explicit biome based assessments of the local ecological drivers of bacterial biodiversity.

Sensitization of human bladder tumor cells to TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis with a small molecule IAP antagonist - Thomas S. Griffith; Tamara A. Kucaba; Michael A. O’Donnell; Jennifer Burns; Christopher Benetatos; Mark A. McKinlay; Stephen Condon; Srinivas Chunduru (Apoptosis, 2011)

Benzonatate Ingestion Reported to the National Poison Center Database System (NPDS) - Mark L. Winter; Henry A. Spiller; Jill R. K. Griffith (Journal of Medical Toxicology, 2010)

Following the chain to elusive anglers - Shane P. Griffiths; Kenneth H. Pollock; Jeremy M. Lyle; Julian G. Pepperell; Mark L. Tonks; William Sawynok (Fish and Fisheries, 2010)
Obtaining reliable estimates of important parameters from recreational fisheries is problematic but critical for stock assessment and effective resource management. Sampling methodologies based on traditional design‐based sampling theory, is inadequate in obtaining representative catch and effort data, social or demographical characterization, or fisher behaviour from small hard‐to‐reach components within recreational fisheries (e.g. specialized sport fisheries) that may account for the majority of the catch for some species. A model‐based approach to sampling is necessary. Researchers in other disciplines including epidemiology and social sciences routinely survey rare or ‘hidden’ populations within the general community by penetration of social networks rather than by interception of individuals. We encourage fisheries researchers to rethink survey designs and consider the social elements of recreational fishing. Employing chain‐referral methods, such as respondent‐driven sampling (RDS), may be a statistically robust and cost‐effective option for sampling elusive sub‐elements within recreational fisheries. Chain‐referral sampling methodology is outlined and an example of a complemented ‘RDS‐recapture’ survey design is introduced as a cost‐effective application to estimating total catch in recreational fisheries.

Patient preferences and National Health Service costs: a cost-consequences analysis of cancer genetic services - Gethin L. Griffith; Rhiannon Tudor Edwards; J. Mark G. Williams; Jonathon Gray; Val Morrison; Clare Wilkinson; Jim Turner; Barbara France; Paul Bennett (Familial Cancer, 2009)

Effects of the H3 antagonist, thioperamide, on behavioral alterations induced by systemic MK-801 administration in rats - Mark E. Bardgett; Megan Points; John Roflow; Meredith Blankenship; Molly S. Griffith (Psychopharmacology, 2009)

Integrating Agricultural Landscapes with Biodiversity Conservation in the Mesoamerican Hotspot - CELIA A. HARVEY; OLIVER KOMAR; ROBIN CHAZDON; BRUCE G. FERGUSON; BRYAN FINEGAN; DANIEL M. GRIFFITH; MIGUEL MARTÍNEZ‐RAMOS; HELDA MORALES; RONALD NIGH; LORENA SOTO‐PINTO; MICHIEL VAN BREUGEL; MARK WISHNIE (Conservation Biology, 2008)

Neutrophils and TRAIL: insights into BCG immunotherapy for bladder cancer - Mark P. Simons; William M. Nauseef; Thomas S. Griffith (Immunologic Research, 2007)

A field extruder for rapidly sectioning near-surface cores from lakes and wetlands - Paul H. Glaser; Mark Griffith (Journal of Paleolimnology, 2007)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)